Diamine Ligands for Asymmetric Catalysis: Facile Synthesis of C2-Symmetric Piperazines from Seebach’s Oxazolidinone - Kałuża, Zbigniew; Ćwiek, Rafał; Dygas, Mirosław; Kalicki, Przemysław (Synlett, 2014)
C2-Symmetrical hemiaminal ethers and diamines with a piperazine core were synthesized starting from Seebach’s oxazolidinone. The new methodology is based on the dimerization of α-amino aldehydes to bicyclic bishemiaminal ethers, followed by reduction to the corresponding diamines. Several enantiopure piperazine derivatives bearing either methyl or bulky groups including isopropyl and aryl at the bridgehead carbon atoms were obtained applying this methodology. Initial screening of new ligands in the copper-catalyzed asymmetric acylation of meso-1,2-diols produced promising results (up to 92% ee).
Keywords: asymmetric synthesis; catalysis; diamine ligands